Descriptive Comparison of Hispanic Doctoral Students (2007-2014) with Carnegie Initiative of the Doctorate National Survey Results - Morgan, Bobbette M.; Alcocer, Luis F. (American Journal of Education and Learning, 2016)
One hundred doctoral students and graduates of a doctoral program in education on the Mexico border were asked to complete a survey developed by the Carnegie Initiative on the Doctorate (CID). According to the CID developers, Walker, Golde, Jones, Bueschel and Hutchings, “the purpose of the survey is to examine the relationship between student experiences in a doctoral program and the outcomes of doctoral education. The survey addresses the full range of responsibilities which may be expected of a holder of the doctorate including research, teaching, and the application of knowledge and skills in the discipline to practical problems in the world outside the university.” Fifty percent of those surveyed responded.